2012
DOI: 10.3892/or.2012.1663
|View full text |Cite
|
Sign up to set email alerts
|

Effects on apoptosis and cell cycle arrest contribute to the antitumor responses of interleukin-27 mediated by retrovirus in human pancreatic carcinoma cells

Abstract: Abstract. Interleukin (IL)-27, composed of p28 and EpsteinBarr virus-induced gene 3 (EBI3) subunits, has diverse functions in regulating immune systems. Human melanoma cells have been shown to express both IL-27 receptor subunits, and growth inhibition by IL-27 was detected. We investigated whether forced expression of the p28-linked EBI3 gene in human pancreatic carcinoma cells (AsPC1) by retroviral vector would produce IL-27-mediated antitumor effects and the related mechanisms. The data demonstrated that As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In general, IL-27 modulates immunologic function that expresses by either proinflammatory or anti-inflammatory effects. In cancer cells, IL-27 can activate apoptosis via several pathways as presented in some reports [35,36]. A549 cell is derived from adenocarcinoma origin.…”
Section: Discussionmentioning
confidence: 99%
“…In general, IL-27 modulates immunologic function that expresses by either proinflammatory or anti-inflammatory effects. In cancer cells, IL-27 can activate apoptosis via several pathways as presented in some reports [35,36]. A549 cell is derived from adenocarcinoma origin.…”
Section: Discussionmentioning
confidence: 99%
“…Both pro-and anti-tumorigenic roles have been suggested for IL-27, depending on the cancer type examined [ 227 , 228 ]. In PDAC, elevated levels of IL-27 correlate with poor overall survival ( Figure 3 J); however, it has been shown that IL-27 overexpression in PDAC cell line xenograft models exhibited reduced tumour growth, due to increased cell cycle arrest and apoptosis, and increased overall survival [ 229 , 230 ]. It was also shown by in vitro co-culture that IL-27 inhibited the polarisation of TAMs towards an M2 phenotype, thereby reducing cancer cell proliferation, migration, and invasion, inducing cancer cell apoptosis, and improving therapeutic response to gemcitabine [ 231 ].…”
Section: Emerging Roles For the Il-6 Family Of Cytokines In Pdacmentioning
confidence: 99%
“…It has previously been reported that IL-27 directly inhibits cell proliferation and angiogenesis in prostate cancer ( 27 ). Furthermore, transfection of human pancreatic carcinoma cells with IL-27 has previously been reported to inhibit proliferation, induce cell cycle arrest and promote apoptosis ( 28 ). Increasing the expression levels of IL-27, combined with treatment with rapamycin and cisplatin, has been demonstrated to inhibit the proliferation and metastasis of endometrial cancer ( 29 ).…”
Section: Discussionmentioning
confidence: 99%